A Case of Duodenal Signet-ring Cell Carcinoma Suspected to Originate in Brunner's gland - Shoko, Tomohisa; Miyamoto, Takeshi; Oshima, Ikuya; Otsuki, Kazunori; Kakuta, Yukio; Ariga, Takamitsu; Yoshimura, Seiji; Ozaki, Masahiko; Kawamura, Shuji; Kinoshita, Hirohisa (Nippon Shokaki Geka Gakkai zasshi, 2003)
A 57-year-old man followed up since 1994 for duodenal polyposis was found in gastrointestinal endoscopy in April 1999 to have duodenal carcinoma. A pathological study of a duodenal biopsy showed poorly differentiated adenocarcinoma. Under a diagnosis of primary duodenal carcinoma, we conducted a pancreaticoduodenectomy. The 1.5×1.2 cm tumor was located orally from the ampulla of Vater in the second portion of the duodenum. The classification was Borrmann type 2. Pathological study showed signet-ring cell carcinoma limited to the proper muscle. Because his duodenal polyposis had ectopic gastric mucosa, we wanted to determine the cancer originated from the ectopic gastric mucosa or duodenal Brunner's gland. Histochemical study using periodic acid-schiff (PAS), concanavalin A (con A) and high iron diamine-alcian blue (HID-AB) revealed that the origine of the carcinoma was suspected to be Brunner's gland.